Measuring next of kin´s experience of participation in the care of older people in nursing homes - Westergren, Albert; Department of Health Sciences, Lund University (Kristianstad University, 2020)
We sought to assess the measurement properties of items aimed at operationalizing participation in care by next of kin, applied in nursing homes.

Data file 1: SPSS file (.sav) with sex, age category, contact person, 37 items aimed to capture participationin care.
Data file 2: Excel (.xlsx) transformation tables from raw total scores, to linear logits, to linearised total scors with the same range as the original scores.
Data file 3: File (.rum) for Rasch model analysis, prepared for RUMM2030.

Utveckling av ett instrument för att mäta närståendes upplevelser av deltagande i vården av äldre personer på särskilda boenden.

Datafil 1: SPSS fil (.sav) med kön, ålderskategori, kontaktperson, 37 items som avser att mäta delaktighet i vårdandet.
Datafil 2: Excel (.xlsx) transformeringstabeller från råa totalpoäng, till linjära mått, till linjariserade totalpoäng med samma range som ursprungspoängen.
Datafil 3: Fil (.rum) för Rasch modell analys av item data, producerad för RUMM2030.
Närståendes upplevelser av deltagande i vården av äldre personer på särskilda boenden
Keywords: Medical and Health Sciences; Medicin och hälsovetenskap